Echinococcus multilocularis specific antibody, systemic cytokine, and chemokine levels, as well as antigen-specific cellular responses in patients with progressive, stable, and cured alveolar echinococcosis: A 10-year follow-up. - Beate Grüner; Lynn Peters; Andreas Hillenbrand; Patrick Voßberg; Jonas Schweiker; Elisabeth G Rollmann; Laura H Rodriguez; Jasmin Blumhardt; Sanne Burkert; Peter Kern; Carsten Köhler; Peter T Soboslay (Public Library of Science (PLoS), 2022)
Background The infestation with Echinococcus multilocularis larvae may persist in humans for up to decades without evident clinical symptoms. Longitudinal investigations are needed to understand the dynamic immunological processes in alveolar echinococcosis (AE) patients associated with an active and progressive, a stable or a regressive course of disease. Methodology/principal findings This study evaluated the E. multilocularis specific antibody responses, systemic cytokine, and chemokine serum levels over a 10-year follow-up period, as well as cellular responsiveness in AE patients. Our results demonstrate a rapid decrease in antibodies against E. multilocularis specific antigen Em2+. Especially in cured patients, these antibodies remained negative, making them a significant predictor for cured AE. E. multilocularis specific IgG4, and indirect hemagglutination IHA decreased later in time, after around 5 years. While total IgE did not show significant dynamics over the course of disease, E. multilocularis specific IgE decreased after one to two years, and increasing levels were a significant predictor of progressive disease. There was no significant change in systemic IL-8, IL-9, CCL18 or CCL20 serum levels over time. Univariate analysis across groups indicated lower IL-8 levels in cured patients; however, this result could not be confirmed by multivariate analysis. Levels of CCL17 decreased during treatment, especially in cured patients, and thus might serve as a predictive or risk factor for progressive disease. Levels of IL-10 and CCL13 decreased during disease, especially after five and ten years of intervention. The E. multilocularis antigen (EmAg) inducible cellular productions of MCP1(CCL13), TARC(CCL17) and PARC(CCL18) were lowest in patients with cured AE and infection-free controls, while the EmAg inducible cellular production of IFN-γ increased after cure. Significant positive cytokine and chemokine correlations were observed in AE patients for IL-9, IL-10, CCL13(MCP-4), CCL17(TARC) and CCL20(LARC)(for all p<0.001). E. multilocularis specific IgG4 response correlated positively with TARC (p<0.001). Both markers enhanced over time in progressive disease and decreased after cure. The levels of IL-8, IL-10, MCP4 and LARC enhanced with AE regression. Conclusions/significance Repeated biomarker surveys are advisable to evaluate progression or regression of disease during longitudinal follow-up and such analyses can support imaging techniques and improve staging of AE patients.